Methodology of Using Video for Teaching English - Klimova, Olena; Cherednichenko, Galina (My University, 2013)
The article deals with the problems of video films’ usage on the lessons of English. Creation and application of Methodological Materials for working with this film at the English lessons has been analyzed. Examples of tasks and the system of exercises to the film are shown. These Methodological Materials give the opportunity to use the film at the lessons, as well as for work at home. The authors consider the work aimed to demonstrate the efficiency of such methodology. В статті представлено методику використання навчальних відеофільмів на прикладі відео курсу «Business English Portfolio» на заняттях з англійської мови. Продемонстровано застосування методичних рекомендацій, створених спеціально для опрацювання цього відеофільму. Методичні рекомендації дають змогу використовувати відео курс під час занять, для домашньої та самостійної роботи студентів. Показано приклади завдань, описано систему вправ. Використання даних методичних рекомендацій дозволяє зробити висновок про ефективність такої методики.
Keywords: іноземна мова; методика; відеофільм; система вправ; foreign language; methodology; video film; system of exercises; methodology of usage; кафедра ділової іноземної мови та міжнародної комунікації